Territory: An Unknown Quantity in Debates on Territorial Cohesion - Andreas Faludi (Politecnico di Torino, 2013)
There are complaints about territorial cohesion being a vague concept, but in relevant debates territory, too, figures as an unknown quantity. Thus, is it the fixed property of any state, region or local administrative unit, or is it a malleable social construct; rather than being filled with bounded territories, does space overall contain a dynamic network with fuzzy internal, as well as external boundaries, with implications for territorial cohesion? After all, if the former were to be true, territorial cohesion would refer to qualities of what is inside bounded territories. If it were to be the latter, then the meaning of territorial cohesion would include qualities of the relations within a complex network of socially constructed, sometimes ephemeral constructs. There are implications for the ways subsidiarity and multi-level governance are invoked in EU discourse where there is a similar failure to question the underlying notion of territory. What is relevant here is the distinction between a ‘territorial’ and ‘relational’ geography. Considered opinion suggests that these alternatives can and, in view of the persistence of the principle of territorial representation, must be reconciled. However, though firmly entrenched, some constitutional theorists question the very principle. The debate is far from conclusive but at least it shows that discussion, even of this apparently fundamental principle is possible.